Types and Risk Factors of Male Infertility in Benghazi Teaching Hospital for Fertility and Assisted Reproduction. Cross sectional study - Elsaid, Amina; Eltajouri, Aynoor; Benismail, Ali; Ellafi, Abaq; Ajoudah, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2026)
Male infertility is a significant global health concern, accounting for 40–50% of infertility cases in couples. Despite its prevalence, limited research has been conducted on the causes and risk factors of this condition in Libya. The aim is to determine the types of infertility in men as well as to determine the socio-demographic and behavioral risk factors in infertile men from Benghazi who have been referred to Benghazi Teaching Hospital for Fertility and Assisted Reproduction. A hospital-based cross-sectional study was conducted, including male patients who were referred to the hospital between 2022 and 2023. Among the 99 participants, 48.5% were aged 36–46 years, and 61% had primary infertility. Semen abnormalities were prevalent, with oligospermia (30.3%), asthenospermia (27.3%), and teratospermia (15.2%) as the most common. Smoking was reported by 52.5% of participants, obesity by 19.2%, and varicocele by 18.2. Semen abnormalities and modifiable risk factors, particularly varicocele, are major contributors to male infertility at Benghazi Hospital.